Sympathetic postganglionic cholinergic fibres - Burn, J. H. (1960)
When the postganglionic fibres to the nictitating membrane are stimulated in a cat treated with reserpine, the membrane contracts. The contraction is increased after the injection of eserine and is abolished with atropine. Thus the fibres stimulated appear to be cholinergic. When the splenic nerve is stimulated in a cat treated with reserpine there is similar evidence of the presence of cholinergic fibres; the spleen dilates, the dilatation is greater in the presence of eserine and is abolished by atropine. The hypogastric nerves when stimulated cause inhibition of the uterus of the virgin cat. When the cat is treated with reserpine, stimulation then causes contraction which is increased in the presence of eserine and abolished by atropine. There is also evidence of cholinergic fibres in the postganglionic supply to the vessels of the rabbit's ear. From this and other evidence it is suggested that a form of adrenergic mechanism may exist such that cholinergic fibres in the postganglionic sympathetic supply liberate acetylcholine; this in turn liberates noradrenaline from a store around the sympathetic nerve ending.